Предмет: Алгебра,
автор: Asd14qwer
решите уравнение помогите
Приложения:
Ответы
Автор ответа:
0
(3x+1)/(x+2)=1+(x-1)/(x-2)
x≠-2 x=2
(3x+1)(x-2)=(x+2)(x-2)+(x-1)(x+2)
3x²-6x+x-2-x²+4-x²-2x+x+2=0
x²-6x+4=0
D=36-16=20
x1=(6-2√5)/2=3-√5
x2=3+√5
x≠-2 x=2
(3x+1)(x-2)=(x+2)(x-2)+(x-1)(x+2)
3x²-6x+x-2-x²+4-x²-2x+x+2=0
x²-6x+4=0
D=36-16=20
x1=(6-2√5)/2=3-√5
x2=3+√5
Похожие вопросы
Предмет: Математика,
автор: tomilin26
Предмет: Математика,
автор: Uiovvggcxfvv
Предмет: Окружающий мир,
автор: nikiforovnikita08
Предмет: Химия,
автор: SadBoy1337